Apoptotic Potential of Secretome from Interleukin-Induced Natural Killer Cells toward Breast Cancer Cell Line by Transwell Assay - Wahyu Widowati; Diana Krisanti Jasaputra; Teresa Liliana Wargasetia; The Fransiska Eltania; Alya Mardhotillah Azizah; Mawar Subangkit; I Nyoman Ehrich Lister; Chrismis Novalinda Ginting; Ermi Girsang; Ahmad Faried (Bogor Agricultural University, Indonesia, 2020)
Breast cancer (BC) is the number one cause of deaths from cancer in women. Metastasis in BC is caused by immunosurveillance deficiency, including impairment of Natural Killer (NK) cell maturation, low NK activity, and decreasing cytotoxicity. This study was performed to improve activating receptors and cytotoxicity of NK cells using interleukin 15 (IL15) against BC cells. Human recombinant IL15 was used to induce NK cells. To evaluate the potential of IL15 in inducing NK cells, we measured the activating and inhibiting receptors (NKG2D, NKG2A), apoptotic potency of NK cells on BC cells (MCF7) using transwell assay. The IL15 inducer on the NK cell were measured NKG2D, NKG2A gene expression with quantitative polymerase chain reaction (qPCR), (GzmB) secretion using ELISA, apoptotic gene expression of MCF7 using qPCR. IL15 increased NKG2D expression 4.01-9.13%, but IL15 could not affect toward NKG2A expression on NK cells. IL15-activated NK cells, inhibited BC cells proliferation, induced apoptotic BC cells 25.89-32.19%, induced apoptotic genes of BC cells bax, p53. IL15 increase NK activating receptor (NKG2D), inhibit BC cells proliferation, induce apoptotic percentage and induce apoptotic gene expression.